2004
DOI: 10.1308/147870804155
|View full text |Cite
|
Sign up to set email alerts
|

Malignant eccrine poroma in breast cancer-related lymphoedema

Abstract: We describe the first case of malignant eccrine poroma arising in a lymphoedematous site. The patient had long-standing lymphoedema of the upper limb following breast cancer treatment. Lymphoedema is a recognised complication of breast cancer treatment and a risk factor for the subsequent development of malignancy. Possible mechanisms for this are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Similar observations have been recorded previously. 1,17 Among the cases of mycetoma of the scalp, one was eumycetoma and the other was actinomycetoma. The patient with actinomycetoma also had mild cutis vertis gyrata (with a positive family history).…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations have been recorded previously. 1,17 Among the cases of mycetoma of the scalp, one was eumycetoma and the other was actinomycetoma. The patient with actinomycetoma also had mild cutis vertis gyrata (with a positive family history).…”
Section: Discussionmentioning
confidence: 99%
“…In one of the largest case series of eccrine poromas (45 cases), 16% of the poromas studied arose in areas with antecedent trauma, and since then, eccrine poromas have been described occurring in the setting of electron beam therapy, burn sites, and chronic radiation dermatitis . Documentation in the literature of eccrine poromas arising in lymphedema is sparse to none, although Lynch et al reported a case of porocarcinoma arising in the setting of breast cancer‐related lymphedema …”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the clinical and histologic features of ESFAs overlap with those of eccrine poromas to such an extent that rather than classifying ESFA as a separate entity distinct from poroma, it may be more prudent to consider ESFA as an entity belonging along the continuum of eccrine poroid proliferations, with poroma being associated with a tumorigenic growth pattern and an abundant neoplastic epithelial component while ESFA represents a more typically reactive, reticular proliferation with a robust stromal component. Eccrine proliferations arising in the setting of lymphedema and other reactive settings have been more often classified as ESFAs, although eccrine poromas have been described to occur in similar reactive settings as well . The commonalities between eccrine poromas and ESFAs extend to additional shared features, including benign prognosis, rare incidence of malignant transformation, and indolent biologic behavior that obviates the need for aggressive treatment modalities .…”
Section: Discussionmentioning
confidence: 99%
“…Many malignancies are known to arise on areas of lymphoedema, including Stewart–Treves syndrome, Kaposi sarcoma, non‐Hodgkin lymphoma, B‐cell lymphoma, cutaneous metastases of follicular centre cell lymphoma, anaplastic large‐cell lymphoma, basal cell carcinoma, squamous cell carcinoma, melanoma, malignant fibrous histiocytoma, and Merkel cell carcinoma . Only one previous case of PC arising on a lymphoedematous limb has been reported, which occurred after axillary lymph‐node dissection for breast cancer …”
Section: Reportmentioning
confidence: 99%
“…5,8 Only one previous case of PC arising on a lymphoedematous limb has been reported, which occurred after axillary lymph-node dissection for breast cancer. 9 We wish to emphasize the role played by trauma (including saphenous venectomy) involving the medial area of the legs in the disruption of lymph drainage of the legs, and the consequent induction of a regional cutaneous area of destabilization that can predispose to the occurrence of neoplasms. Hence, physicians should consider the possibility of tumours in patients who have sustained trauma to the leg or who have undergone orthopaedic surgery on the leg or saphenous venectomy for bypass surgery.…”
Section: Reportmentioning
confidence: 99%